Chứng minh đẳng thức sau: 1 – sinx.cosx = (sin^2 x)/(1 + cot x) + (cos^2 x)/(1+tan x)

Question

Chứng minh đẳng thức sau:
1 – sinx.cosx = (sin^2 x)/(1 + cot x) + (cos^2 x)/(1+tan x)

in progress 0
Peyton 2 giờ 2021-09-07T11:19:52+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-07T11:21:20+00:00

    Đáp án:

     

    Giải thích các bước giải:

    (Sin^2x)/(1+cotx) + (cos^2x)/(1+tanx) 

    =(Sin^2x)/(1+(cosx)/(sinx)) + (cos^2x)/(1+(sinx)/(cosx))

    =(Sin^2x)/((sinx+cosx)/(sinx))+(cos^2)/((cosx)+(sinx))/(cosx)

    =((Sin^3)+(cos^3x))/(sinx+cosx) 

    =(Sinx+cosx)[(sinx+cosx)^2-3sinx.cosx]/(sinx+cosx)

    =Sin^2x+cos^2x+2sinx.cosx-3sinx.cosx

    =1-sinx.cosx

    0
    2021-09-07T11:21:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

    (Sin^2x)/(1+cotx) + (cos^2x)/(1+tanx) 

    =(Sin^2x)/(1+(cosx)/(sinx)) + (cos^2x)/(1+(sinx)/(cosx))

    =(Sin^2x)/((sinx+cosx)/(sinx))+(cos^2)/((cosx)+(sinx))/(cosx)

    =((Sin^3)+(cos^3x))/(sinx+cosx) 

    =(Sinx+cosx)[(sinx+cosx)^2-3sinx.cosx]/(sinx+cosx)

    =Sin^2x+cos^2x+2sinx.cosx-3sinx.cosx

    =1-sinx.cosx

    =>1 – sinx.cosx = (sin^2 x)/(1 + cot x) + (cos^2 x)/(1+tan x)

    cho mik câu trả lời hay nhất nha!!!

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )